Impact Of The National Healthcare Transformation On Healthcare Administration And Workforce In The Light Of Saudi Vision 2030 (The Review of Diabetic Studies, 2024)
Background: Saudi Arabia has launched Vision 2030 as a comprehensive national development plan aimed at transforming multiple sectors, including the healthcare system. A major component of this transformation is the restructuring of healthcare governance, financing, service delivery, and workforce development to improve efficiency, quality, and sustainability.Aim: This study assesses the impact of the national healthcare transformation on healthcare administration and the healthcare workforce in light of Saudi Vision 2030.Method: A systematic review of the literature was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. An initial search yielded 876 articles on Saudi Vision 2030 and healthcare transformation, with a particular focus on healthcare administration and workforce development. An additional eight studies were identified through manual searching. After applying predefined inclusion and exclusion criteria, 12 studies were selected for final analysis. The review included peer-reviewed articles, policy documents, and official reports, and a thematic synthesis approach was used to analyze the findings.Results: The findings indicate that Vision 2030 has led to major legislative and structural reforms in the healthcare sector, particularly through privatization initiatives and public–private partnerships (PPPs). Increased investment in healthcare has improved infrastructure, service quality, and the adoption of advanced medical technologies. Education and training systems have been strengthened to equip healthcare professionals with the skills required for the new model of care. However, gaps remain in healthcare workers’ knowledge, readiness, and adaptation to the transformed healthcare system. Furthermore, governance reforms aligned with international sustainability goals have enhanced institutional capacity and system accountability.Conclusion: Saudi Vision 2030 has brought substantial changes to healthcare administration and the healthcare workforce through policy reforms, modernization strategies, and governance restructuring. However, the successful implementation of these reforms requires continuous professional development, effective integration of digital health technologies, and supportive regulatory frameworks. Healthcare administration and leadership must continue to adapt strategically to ensure high-quality service delivery and the long-term success of Vision 2030 healthcare objectives.